Publicidade e o direito à proteção à infância e à adolescência em meio à sociedade de consumo - Araruna, Simone Bezerra Pontes (2018)
This Master's dissertation is based on the observation of the Principle of Absolute Priority in relation to children and adolescents, guaranteed in article 227 of the Brazilian Federal Constitution of 1988, the other constitutional and infraconstitutional principles incorporated into the Brazilian normative system concerning the integral protection of childhood, as well as the reporting principles of the advertising activity of the Code of Consumer Protection, which together corroborate to ensure the integral development of the child and the adolescent. Therefore, we evaluate the advertising phenomenon that has progressively and exponentially approached the child and the adolescent, in order to use them as propellants and absorbers of consumption, from the perspective of the interference of consumer society and consumer culture . Based on these considerations, we examine the negative repercussions of publicity harassment in the formation and biopsychosocial development of children and adolescents, based on three representative examples: obesity, shortening of childhood and social marginality of the poor child. In the end, it is analyzed, from the perspective of the shared responsibility of the family, society and State, evoked by the aforementioned art. 227 of the Federal Constitution of 1988, a panorama on how the concept of child protection with regard to advertising in the Brazilian context has been incorporated and what its direction for the future has been incorporated. For this purpose, a descriptive research was carried out, of a qualitative nature, based on the method of theoretical, historical and bibliographic procedures, based on direct and indirect documentation and studies already carried out on the subject.